Is gingival crevicular fluid volume sensitive to orthodontic tooth movement? A systematic review of split‐mouth longitudinal studies. (17th September 2012) - Perinetti, G.; Primožič, J.; Castaldo, A.; Di Lenarda, R.; Contardo, L.
<x xml:space="preserve">Abstract</x> Perinetti G., Primožič J., Castaldo A., Di Lenarda R., Contardo L. Is gingival crevicular fluid volume sensitive to orthodontic tooth movement? A systematic review of split‐mouth longitudinal studies Orthod Craniofac Res 2013; 16:1–19. © 2012 John Wiley & Sons A/S Abstract To assess the scientific evidence for detectable volume changes of gingival crevicular fluid (GCF) incident to orthodontic tooth movement (OTM). A literature survey of longitudinal split‐mouth studies was performed searching PubMed, SCOPUS and the Cochrane Library, with the last access in 15 April 2012. After selection, 13 articles qualified for the final analysis. One study was judged to be of medium/high quality, six were of medium quality and the rest of low quality. Across all studies, there was very little or no statistically significant change in GCF volume incident to OTM. The changes seen were generally ascribed to the clinical or subclinical inflammation consequent to placement of the fixed orthodontic appliance. A reappraisal of the data provided in these studies was performed by comparing the GCF volume from the test (moved) and control (non‐moved) teeth, in terms of effects‐size (ES) coefficients and variations, as percentages. Generally, the ES coefficients and the variations were below 1.0 and 20%, respectively. Therefore, when using current methods to collect and measure GCF volume, there was no meaningful diagnostic potential for the GCF volume as an index of tissue remodelling incident to OTM. The GCF volume is not a reliable index for tissue remodelling incident to OTM.